Emotional dissonance, job stress, and intrinsic motivation of married women working in call centers: The roles of work overload and work-family conflict - Moo-Kyeong Jeon; Hyun Joong Yoon; Yuha Yang (Administrative Sciences, 2022)
This research was designed to test and extend the model of emotional dissonance. Previous models of emotional dissonance, such as the Job Demand-Resource (JD-R) and the Stress-Strain-Outcome (SSO) models, are limited in that they do not account for the influences of work and work-family-related conflicts. The present paper focused on emotional labor carried out by married women working in call centers. We developed the model of emotional dissonance influencing intrinsic motivation and job stress, with the moderating effects of work overload and work-family conflict. The data of 468 employees analyzed using least square regression showed that that emotional dissonance is positively related to job stress, but is negatively related to intrinsic motivation. Both work overload and work-family conflict were found to be significant moderators that aggravate the positive relationships between emotional dissonance and job stress, and the negative relationships between emotional dissonance and intrinsic motivation. Theoretical and practical implications on emotional labor and emotional dissonance are discussed.
Keywords: 350; call center; emotional dissonance; intrinsic motivation; job stress; work overload; work-family conflict